2019
DOI: 10.1155/2019/9075862
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of Low-Rank Coal Pyrolysis by Model-Free and Model-Fitting Methods

Abstract: Coal SJC, coal WJG, coal ZJM, and coal HCG were selected to investigate the pyrolysis kinetics of northern Shaanxi coals. TG and DSC experiments of four coals were carried out with a synchronous thermal analyzer at heating rates 5, 10, 15, and 20 C/min, respectively. The pyrolysis characteristics were described by thermogravimetric data, and the kinetic parameters were calculated by Flynn–Wall–Ozawa (FWO), Kissinger, general integration, and MacCallum–Tanner methods. The results show that coal SJC, coal ZJM, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…ese extractives are composed of fatty acids, steroids, and aliphatic compounds and these extractives can improve the liquid fuel properties such as viscosity and heating value and can provide ease in phase separation of liquid fuels. Sewage sludge contains a relatively higher nitrogen content than lignocellulosic biomass [96]. is comes from the protein fragments of samples and can favor its usage in fertilizer [97].…”
Section: Ultimate Proximate and Chemical Composition Analysis Of Sewage Sludgementioning
confidence: 99%
“…ese extractives are composed of fatty acids, steroids, and aliphatic compounds and these extractives can improve the liquid fuel properties such as viscosity and heating value and can provide ease in phase separation of liquid fuels. Sewage sludge contains a relatively higher nitrogen content than lignocellulosic biomass [96]. is comes from the protein fragments of samples and can favor its usage in fertilizer [97].…”
Section: Ultimate Proximate and Chemical Composition Analysis Of Sewage Sludgementioning
confidence: 99%
“…[2] In China, the annual yield of plastic has exceeded seventy million tons. [3] It is estimated that the annual yield of tires is over 3 million, and it has a growth rate of 4% due to the market demand. [4] The most common plastic types account for over 90%, including polyethylene (PE), polystyrene (PS), polypropylene (PP), polyvinyl chloride (PVC), and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al studied the pyrolysis behavior and kinetics of typical mixed plastics (PP, PE, PVC, PS, and acrylonitrile-butadiene-styrene copolymer) via thermogravimetric analysis, model-free method, and model-fitting method. [3] They found that the mixture of plastic caused differences in apparent activation energy and hence affected the consumption of energy of large-scale pyrolysis treatment. Xuan et al [9] explored the pyrolysis behavior of mixed PP, PE, and PS.…”
Section: Introductionmentioning
confidence: 99%